MENDESAIN MULTIMEDIA PEMBELAJARA DESIGN THE MULTIMEDIA LEARNING OF MATHEMATICS USING GUI MATLAB - Safwandi (Jurnal Dimensi Matematika, 2020)
GUI (Graphical User Interface) is a MATLAB tool as multimedia or a tool that can be used in learning mathematics. MATLAB is a high-performance programming language for computing science or mathematical problems. MATLAB integrates computation, algorithm building, data acquisition, modeling, simulation and prototyping, data analysis, exploration, visualization. The GUI toolbox available in MATLAB can be used to build multimedia applications for learning mathematics. With graphic objects such as buttons, text boxes, sliders, menus and others, it helps someone design mathematics learning media as desired.